2016
DOI: 10.1021/acs.langmuir.5b04619
|View full text |Cite
|
Sign up to set email alerts
|

Conformations of Myoglobin-Derived Peptides at the Air–Water Interface

Abstract: The conformational change exhibited by proteins at liquid interfaces, such as the airwater and oil-water interfaces, has long been of interest, both for understanding protein structure outside of native environments and for applications in areas including food technology and pharmaceuticals. Using molecular simulation this paper studies the conformations of two peptides derived from myoglobin, for which the emulsification behaviour has been studied. Both peptides were found to readily adsorb onto the air-water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
48
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(56 citation statements)
references
References 66 publications
8
48
0
Order By: Relevance
“…It is also similar to recent simulations of myoglobin-derived peptides, where both compact and globular states were found 33 . The lack of significant tertiary structure change is also seen in the locations of the residues (Figure 7(b)) which are essentially the same as for the NpT simulations.…”
Section: Dce Interfacesupporting
confidence: 90%
See 2 more Smart Citations
“…It is also similar to recent simulations of myoglobin-derived peptides, where both compact and globular states were found 33 . The lack of significant tertiary structure change is also seen in the locations of the residues (Figure 7(b)) which are essentially the same as for the NpT simulations.…”
Section: Dce Interfacesupporting
confidence: 90%
“…Recently replica exchange simulations of lysozyme at the water-dichloroethane interface showed that this can adopt a number of conformations of similar free energy 32 . Simulations of peptides derived from myoglobin also found that these exhibit a number of different interfacial conformations, with the preferred orientation for the two peptides investigated being consistent with their differing emulsification behaviour 33 .…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…Recently replica exchange simulations of lysozyme at the water-dichloroethane interface showed that this can adopt a number of conformations of similar free energy 32 . Simulations of peptides derived from myoglobin also found that these exhibit a number of different interfacial conformations, with the preferred orientation for the two peptides investigated being consistent with their differing emulsification behaviour 33 .…”
Section: Introductionmentioning
confidence: 68%
“…The Gromos54a7 force field 45 was used for modelling the proteins and along with SPC water 46 . The Gromos family of force fields have been parameterised against solvation free energies for amino acid side chains 45,47 so may be expected to give a good description of the partitioning of these between water and hydrophobic media and have been used in a number of previous studies of proteins at liquid interfaces 20,21,33,48,49 .…”
Section: B Methodologymentioning
confidence: 99%